NUMERICAL STUDY OF WATER ADDITION ON THE COMBUSTION CHARACTERISTICS IN AN HCCI ETHANOL ENGINE - Telli, G. D.; Rosa, J. S.; Costa, C. A.; Rocha, L. A. O. (Revista de Engenharia Térmica, 2022)
Low-temperature combustion modes have attracted global attention in recent years, especially the homogeneous charge compression ignition (HCCI) mode. The HCCI combustion produces high-speed combustion, achieving relatively high thermal efficiencies while emitting low NOX and soot. However, due to the lack of direct control to start the combustion, one of the main challenges in this type of engine is to ensure that auto-ignition occurs close to the top dead center for a wide operation range. There are a few combustion phase control techniques to solve this limitation, and one of them is water injection. In this regard, this paper explores the influence of water concentration in an ethanol HCCI engine as a form of combustion phasing control. The work was conducted numerically using a zero-dimensional single-zone model with a chemical kinetic mechanism containing 56 species and 383 reactions. The numerical model results were well agreed with the reported experimental data. The water fraction ranged from 0 to 18% by mass at 3% intervals. The results demonstrate that water injection is an efficient strategy to control the combustion phasing by adjusting the charge reactivity. The increase in water fraction reduced in-cylinder pressure and heat release rates. Furthermore, the combustion phase was advanced, the combustion duration was extended, and thermal efficiency was about 44.3% with the increase in water concentration.